2009
DOI: 10.1021/ja905795v
|View full text |Cite
|
Sign up to set email alerts
|

Urea Destabilizes RNA by Forming Stacking Interactions and Multiple Hydrogen Bonds with Nucleic Acid Bases

Abstract: Urea has long been used to probe the stability and folding kinetics of proteins. 1 In contrast only recently it was shown that the RNA molecules that have a high propensity to misfold can be resolved using moderate amounts of urea. 2 Urea titrations can also be used to probe the interactions that stabilize the folded states of RNA. 2c Although the mechanism by which urea denatures proteins is now fairly well understood 3 the nature of interactions by which urea destabilizes RNA is not known. In order to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 34 publications
(32 reference statements)
9
96
0
Order By: Relevance
“…The urea molecule has the ability of forming more favorable dispersion interactions with the protein than water has, hence being able to dissolve the (mostly) hydrophobic core regions of a protein, while at the same time having the ability of forming strong electrostatic interactions (hydrogen bonds) with the solvent. A similar mechanism has also been observed for the denaturation of RNA (Priyakumar et al 2009). Another piece of evidence for the amphiphilic properties of urea is that molecular modeling has shown an increase of urea concentration close to model hydrophobic surfaces (Koishi et al 2010) and inside hydrophobic nanotubes (Xiu et al 2011).…”
Section: Urea-cellulose Interactions In Relation To Urea-induced Protsupporting
confidence: 72%
“…The urea molecule has the ability of forming more favorable dispersion interactions with the protein than water has, hence being able to dissolve the (mostly) hydrophobic core regions of a protein, while at the same time having the ability of forming strong electrostatic interactions (hydrogen bonds) with the solvent. A similar mechanism has also been observed for the denaturation of RNA (Priyakumar et al 2009). Another piece of evidence for the amphiphilic properties of urea is that molecular modeling has shown an increase of urea concentration close to model hydrophobic surfaces (Koishi et al 2010) and inside hydrophobic nanotubes (Xiu et al 2011).…”
Section: Urea-cellulose Interactions In Relation To Urea-induced Protsupporting
confidence: 72%
“…This substantiates the results from previous MD studies that reported stacking interactions between nucleobases and urea. 1819 …”
Section: Resultsmentioning
confidence: 99%
“…1819 A recent MD study on urea induced unfolding of flavin adenine dinucleotide reported the presence of stacking interactions between the adenine moiety of FAD and urea. 20 However, the nature of such stacking interactions and their role in stabilizing the nucleic acid bases in the unfolded state are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the results show that even water-miscible fragments can cause target denaturation on the timescale of the MD simulations used to probe for fragment binding, as should be anticipated from MD studies probing the atomic details of, for example, urea- or guanidinium-induced protein 50 and nucleic acid denaturation. 51 Thus, the methodologies described for preventing target denaturation and for identifying and excluding denaturing trajectories from analysis are anticipated to be useful for both hydrophobic and hydrophilic fragment-based computational approaches to inhibitor discovery.…”
Section: Discussionmentioning
confidence: 99%